Promises, image concerns, and excuses–An experimental investigation - Grubiak, Kevin P. (Frontiers in Behavioral Economics, 2025)
This paper tests the robustness of promise keeping in economic interactions using a laboratory experiment. Our design allows us to examine the roles of both social- and self-image concerns, and to investigate whether these concerns are diminished when participants are provided with responsibility-diffusing excuses. When the responsibility for a broken promise is undeniable, promise keeping is high. However, when plausible excuses are available that allow participants to preserve their social image, a significant number choose to break their promises. Yet, cooperation remains higher compared to treatments without a communication stage, and we find no evidence of participants engaging in self-deception to evade their promise-induced commitments. These findings suggest that while some individuals keep their promises reluctantly, others exhibit stable preferences for promise keeping that are not easily eroded by moral wiggle room.